Environmental Perceptions of Gifted Secondary School Students Engaged in an Evidence-Based Enrichment Practice. (July 2018) - Brigandi, Carla B.; Weiner, Jennie M.; Siegle, Del; Gubbins, E. Jean; Little, Catherine A.
Grounded in the Achievement Orientation Model, this qualitative case study examines participation in enrichment and environmental perceptions of gifted secondary school students. Participants included 10 gifted secondary school students, their parents, and their classroom teacher. Data included student, parent, and teacher responses in semistructured interviews, short answer surveys, and student work. Findings indicated a relationship between participation in enrichment and environmental perceptions. Student participants benefited from a teacher trained in gifted education who nurtured both affective and cognitive development, homogeneous grouping with like-minded peers, involved parents, and relationships with project mentors. These findings have implications for designing learning environments that effectively support the special needs of gifted secondary school learners.